Endoscopic transforaminal lumbar microdiscectomy. A retrospective analysis of 180 clinical cases - Piontkovskyi, V. K.; Fishchenko, I V (Pain medicine, 2018)
The authors performed retrospective analysis of 180 clinical cases of surgical treatment of lumbar herniated discs in patients who underwent endoscopic transforaminal microdiscectomy. This technique allows minimally invasive insertion of the endoscope into the spinal canal under local anaesthesia to decompress the nerve root by removing hernial protrusion under visual control. However, this technique is not universal and cannot be applied to all patients. Considerable practical experience has shown that the surgeon may encounter certain technical difficulties in cases of cranial or caudal sequester migration and in some cases when the access at L5–S1 level is complicated due to the high standing of the iliac crest. However, if there are correct indications, this technique allows to solve the problem of radicular compression syndrome in a short time.